A decentered study of (un)collaborative governance - Amanda Crompton; Justin Waring (2025)
Purpose: This paper examines the challenges of achieving collaborative governance in public decision-making, particularly in contexts where multiple, conflicting interests are present. It explores the governance dilemmas faced by public leaders who must navigate these tensions while still aspiring to collaborative ideals.Design: Adopting a decentred perspective, the study draws on three qualitative case studies within the English healthcare system. It investigates how policy leaders facilitated structured opportunities for collaboration and how these were influenced by competing traditions and interests.Findings: Despite efforts to enable collaboration, the case studies revealed that decision-making was often shaped by dominant policy leaders, impression management, and persistent conflict. The analysis identifies three forms of “un-collaborative governance”:• Auditable un-collaboration, where formal procedures are used to create an appearance of collaboration while marginalizing dissenting views;• Authoritative un-collaboration, where public leaders control information and agenda-setting to dominate decision-making;• Adversarial un-collaboration, where competition and critique between stakeholders are actively encouraged. These modes can coexist or evolve throughout policy cycles as leaders attempt to fulfil the symbolic or practical expectations of collaboration.Originality: The paper contributes a novel typology of un-collaborative governance, challenging assumptions about the feasibility and desirability of collaboration in complex policy environments. It offers a nuanced account of how collaboration is shaped, constrained, and sometimes subverted by competing institutional logics and strategic behaviour.